1998
DOI: 10.1038/bjc.1998.54
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of paclitaxel in heavily pretreated patients with small-cell lung cancer

Abstract: Summary The purpose of the study was to delineate the efficacy and toxicity of paclitaxel (Taxol, Bristol Myers Squibb) in the treatment of drug resistant small-cell lung cancer (SCLC). Patients with SCLC relapsing within 3 months of cytotoxic therapy received paclitaxel 175 mg m-2 intravenously over 3 h every 3 weeks. The dose of paclitaxel was adjusted to the toxicity encountered in the previous cycle. Of 24 patients entered into the study, 24 and 21 were assessable for response and toxicity respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(105 citation statements)
references
References 20 publications
2
99
1
3
Order By: Relevance
“…Recently, topotecan was approved by the U.S. patient relapses while on therapy or has been off therapy fewer than 2-3 months, his response to topotecan or any other chemotherapy regimen is generally <10% [32]. There are multiple single-agent studies demonstrating activity for recurrent SCLC with response rates ranging from 11%-40% [33][34][35][36][37][38]. These agents include irinotecan, docetaxel, paclitaxel, topotecan, vinorelbine, and carboplatin.…”
Section: Second-line Therapymentioning
confidence: 99%
“…Recently, topotecan was approved by the U.S. patient relapses while on therapy or has been off therapy fewer than 2-3 months, his response to topotecan or any other chemotherapy regimen is generally <10% [32]. There are multiple single-agent studies demonstrating activity for recurrent SCLC with response rates ranging from 11%-40% [33][34][35][36][37][38]. These agents include irinotecan, docetaxel, paclitaxel, topotecan, vinorelbine, and carboplatin.…”
Section: Second-line Therapymentioning
confidence: 99%
“…Among the last generation drugs, paclitaxel is particularly noteworthy; this drug is highly active in various malignancies and its documented activity, in refractory patients, makes it especially interesting for testing in SCLC (Smit et al, 1998). The experience with paclitaxel, in the treatment of SCLC, is still limited but promising: available data from literature strongly suggest a high antitumour activity of paclitaxel-based regimens, with toxicity profiles which vary according to the different drugs used in combination.…”
Section: Discussionmentioning
confidence: 99%
“…This drug showed encouraging single-agent activity as second-line treatment: in patients with ED pretreated with CDE as first-line combination, single-agent paclitaxel showed an overall response rate of 29%, which is at the upper level of activity for any single agent in this setting (Smit et al, 1998). An interesting activity was also observed in untreated patients; in the Eastern Cooperative Oncology Group (ECOG) phase II study a 34% remission rate and a 43-week median survival were observed (Ettinger et al, 1995); the North Central Cancer Treatment Group (NCCTG) also reported a 53% response rate in 43 untreated patients (Kirschling et al, 1999).…”
mentioning
confidence: 99%
“…The demonstrated activity of these two new drugs (topotecan and paclitaxel) in the middle 1990s with novel mechanisms of action against SCLC prompted us to reevaluate the hypothesis of alternating noncross-resistant chemotherapy. Although it is debatable whether the drugs employed in our trial truly are noncross resistant, it is clear that both topotecan 8,9 and paclitaxel 10 have activity against SCLC when they are employed as second-line agents in patients who have failed initial therapy with etoposide and cisplatin. We also were encouraged by the high response rate to topotecan and paclitaxel in previously untreated patients.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In a second-line setting, paclitaxel had a 29% response rate in heavily pretreated patients. 10 Those studies suggested that, from a clinical perspective, topotecan and paclitaxel may be noncross resistant with etoposide and cisplatin.…”
mentioning
confidence: 99%